2018
DOI: 10.1080/14992027.2018.1476782
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate training in audiology improves clinicians’ audiology-related cue utilisation

Abstract: At an applied level, the outcomes provide the basis for a cue-based diagnostic assessment tool that can provide both trainee and practising audiologists with detailed feedback concerning their diagnostic skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…However, there is a tendency to target different constructs in isolation, potentially underestimating the interactions that might be afforded by coalescing different aspects of features that comprise a complex system. This targeting of constructs is evident through a range of initiatives including experimental evaluations that assess the impact of changes to system design, evaluations of the impact of safety climate (Griffin and Neal, 2000; Hinckfuss et al, 2015), and organisational culture (Griffin and Curcuruto, 2015), and the development and evaluations of tools to assess and provide feedback on safety-related skills (Watkinson et al, 2018; Wiggins, 2012; Wiggins et al, 2019). The difficulty lies in establishing the nature of the relationships between variables and then isolating causal interactions that might impact performance.…”
Section: Demands For the Workplace Of The Futurementioning
confidence: 99%
“…However, there is a tendency to target different constructs in isolation, potentially underestimating the interactions that might be afforded by coalescing different aspects of features that comprise a complex system. This targeting of constructs is evident through a range of initiatives including experimental evaluations that assess the impact of changes to system design, evaluations of the impact of safety climate (Griffin and Neal, 2000; Hinckfuss et al, 2015), and organisational culture (Griffin and Curcuruto, 2015), and the development and evaluations of tools to assess and provide feedback on safety-related skills (Watkinson et al, 2018; Wiggins, 2012; Wiggins et al, 2019). The difficulty lies in establishing the nature of the relationships between variables and then isolating causal interactions that might impact performance.…”
Section: Demands For the Workplace Of The Futurementioning
confidence: 99%
“…The different tasks have been individually and collectively associated with differences in performance at an operational level (Loveday et al, 2013b). Test-retest reliability (κ = 0.59, p < 0.05) has been demonstrated with power control operators at 6 months intervals (Loveday et al, 2014) and with audiologists at 18 months intervals (Watkinson et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The test–retest reliability of each of the tasks that comprise EXPERTise 2.0 has been demonstrated in the context of audiology (Watkinson et al, 2018), while test–test reliability of classifications based on performance aggregated across the five tasks has been demonstrated in the context of transmission power control (Loveday et al, 2013a). The construct validity of the EXPERTise 2.0 classifications has been demonstrated in transmission and distribution power control (Loveday et al, 2013a; Sturman et al, 2019), software engineering (Loveday et al, 2014), and aviation (Wiggins et al, 2014), while predictive validity has been demonstrated in audiology (Watkinson et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Behavior associated with higher cue utilization has been associated with greater performance across a range of tasks, including radiology (Carrigan et al, 2020), paediatric intensive care (Loveday et al, 2013b), audiology (Watkinson, Bristow, Auton, McMahon, & Wiggins, 2018), and anesthesiology (Crane et al, 2018). However, it is also clear that cue utilization in one context can impact performance in another, related context.…”
mentioning
confidence: 99%